Virilizing adrenocortical carcinoma in a child: A rare enigma - Sipayya, Varuna (Medknow Publications & Media Pvt Ltd, 2012)
Adrenocortical carcinomas are rare tumors with an incidence of one to two cases per million population and are still more rarer in the pediatric age group. Adrenocortical carcinomas can be functional or may be unassociated with syndromes of hormone overproduction. It is very important to differentiate an adrenocortical adenoma from a carcinoma, as both share a large number of phenotypic features, and assess their prognosis, as adrenocortical carcinoma may need an adjuvant therapy. In this communication, we describe the case of a two-year-old boy, who presented with iso-sexual precocious puberty, having features of virilization, which included growth of facial and pubic hair, deepening of voice, and penile growth.